Karakterisasi Sistem Sensor LDR Berdasarkan Perbedaan Panjang Gelombang Cahaya - Nurul Fatma Hidayati; Kholifah, Nurul; Ratna Arum Febrianti; Gladyns Anandita Yasmin (Fakultas MIPA, Universitas Jember, 2024)
LDR is a type of resistor whose resistance value is influenced by light. LDRs can have varying sensitivity and linearity depending on the type of LDR used. LDR light sensors have different sensitivities to each color variation of light that hits them with their respective wavelengths. An LDR with high sensitivity will show a greater change in resistance when there is a change in the level of light received. LDR linearity is a measure of the extent to which its resistance response to changes in light levels is linear or not. This experiment uses two types of circuits, namely series and parallel circuits to obtain current values ​​when the light intensity is varied in order to test the sensitivity and linearity of the LDR sensor. The LED color variations used are white, red, green and blue. The circuit that produces a large current is a parallel circuit, but in a system with red and blue LEDs the opposite happens, there is a small difference which causes the current in the series circuit to be greater. The R square value in the regression value data for voltage and intensity against the resistance of each LED color starting from white, red, green and blue respectively is 0.868747; 0.765793; 0.833222; and 0.798801.